Exploring the relationship of brand avoidance in fast fashion products among generation z - Chow, Evelyn Sum Yee (2024)
The fast fashion industry is a new fashion business model that emerged in recent years due to globalisation. It has been criticised for its harmful contributions to social and environmental issues which has contributed to the emergence of anti-consumption. This study aims to explore the relationship of brand avoidance in fast fashion products among Generation Z. Specifically, it explores a particular form of anti-consumption which is brand avoidance by using the brand avoidance model by Lee et al., (2009). The brand avoidance model consists of 5 dimensions which are experiential avoidance, identity avoidance, moral avoidance, deficit-value avoidance and advertising avoidance. The sample of this study are individuals aged between 18 to 27 years old, otherwise known as the Generation Z because they are considered the largest consumer group of fast fashion products. Data were collected from 350 individuals that are Generation Z and have experience buying from fast fashion brands before such as Zara and H&M through an online survey. IBM SPSS (Statistical Package for Social Sciences) Statistics version 29.0 is used to conduct the statistical analyses. The findings revealed that identity avoidance and advertising avoidance have a relationship in fast fashion products among Generation Z. In simple words, Generation Z avoids a certain brand when it does not fit their personality or personal values and the advertisements were found annoying or untrustable. Overall, this research helps to better clarify the understanding of the brand avoidance behaviour in Generation Z in Malaysia